The Problematic of Legislative Oversight in Nigeria: A Study of Delta State - Ejumudo, Kelly Bryan Ovie; Ikenga, Francis Ayegbunam (Faculty of Law Universitas Negeri Semarang, 2021)
This study examines the problem of legislative oversight in Nigeria using Delta State as a case study. Four research questions were raised to guide the study and four null hypotheses were formulated for the study. The design of the study was a descriptive survey. The population of the study comprised 600 staff in the Delta State House of Assembly. The sample of the study consisted of 245 staff drawn from nine (9) departments using stratified and simple random techniques. The instrument used for data collection was the legislative oversight questionnaire and the collated data were analyzed using mean rating and chi-square. The findings of the study revealed that there is a significant relationship between politics of trade-off and pay-off between the legislators and the executive as well as poor commitment to oversight functions by the legislators and legislative oversight in Delta State. The study equally showed that there is a significant relationship between the culture of corruption as well as perceptual legislative subservience to the executive and legislative oversight in Delta State. The study recommended that that the legislature in Nigeria, particularly in Delta State, should be truly independent rather than operate and seen as a subservient extension of the executive arm of government, a new culture that is void of the politics of trade-off and pay-off between the legislature and the executive, as well as corruption, should be established.